Evaluating the efficiency of enzyme accelerated CO2 capture: chemical kinetics modelling for interpreting measurement results. (1st January 2021) - Parri, Lorenzo; Fort, Ada; Lo Grasso, Anna; Mugnaini, Marco; Vignoli, Valerio; Capasso, Clemente; Del Prete, Sonia; Romanelli, Maria Novella; Supuran, Claudiu T.
Abstract: In this paper, the efficiency of the carbonic anhydrase (CA) enzyme in accelerating the hydration of CO2 is evaluated using a measurement system which consists of a vessel in which a gaseous flow of mixtures of nitrogen and CO2 is bubbled into water or water solutions containing a known quantity of CA enzyme. The pH value of the solution and the CO2 concentration at the measurement system gas exhaust are continuously monitored. The measured CO2 level allows for assessing the quantity of CO2, which, subtracted from the gaseous phase, is dissolved into the liquid phase and/or hydrated to bicarbonate. The measurement procedure consists of inducing a transient and observing and modelling the different kinetics involved in the steady-state recovery with and without CA. The main contribution of this work is exploiting dynamical system theory and chemical kinetics modelling for interpreting measurement results for characterising the activity of CA enzymes. The data for model fitting are obtained from a standard bioreactor, in principle equal to standard two-phase bioreactors described in the literature, in which two different techniques can be used to move the process itself away from the steady-state, inducing transients.